IMPLEMENTATION OF NORMS AND ETHICS IN PUBLIC SERVICES IN INDONESIA - Herabudin, Herabudin (LPPM STIE Muhammadiah Bandung, 2022)
The fulfillment of basic needs for every community is to provide good public services. As customers, the public hopes to receive professional performance from the public service provider. One form of professionalism is good ethics in public services. This study aims to be able to see how ethics in public services in Indonesia. This research will be carried out using a qualitative approach through the study center method. The data used in this study came from various research results and previous studies that are still relevant to this research. This study then found that there needs to be a synergy between actors to determine ethical and moral values in implementing public services.